Acid-Base and Electrolytes Profile in Critically Ill Pediatric Patients Admitted to Pediatric Intensive Care Unit (PICU) - Khairunnisa, Alya Roosrahima; Peryoga, Stanza Uga; Widiasta, Ahmedz (Majalah Kedokteran Bandung, 2025)
Critically ill pediatric patients are known to experience more frequent episodes of acid-base and electrolyte imbalances when compared to adults, which can significantly impact morbidity and mortality with higher mortality rates and longer hospital stays. Data on the profile of acid-base and electrolyte imbalances in critically ill pediatric patients is very limited in Indonesia. This study was conducted to describe the electrolytes and acid-base profile of critically ill pediatric patients admitted to the Pediatric Intensive Care Unit (PICU). This was a cross-sectional study using secondary data from medical records of critically ill pediatric patients aged 1 month to 18 years admitted to the PICU of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from January 1 to December 31, 2021. Results indicated that 131 (50.8%) of 258 patients experienced electrolytes and acid-base imbalances. The majority of patients were boys (53.0%) and infants (32.8%). The most common primary diagnosis was respiratory (28.2%), central nervous system (19.8%), and gastrointestinal disorders (15.3%). A total of 366 electrolyte imbalance events and 111 acid-base imbalance events were recorded. The most common electrolyte imbalance events were hyponatremia (75.6%), hypocalcemia (48.9%), and hypokalemia (42.7%), respectively, while the most frequent acid-base imbalance events were respiratory alkalosis (33.6%) and metabolic acidosis (21.4%). Electrolyte and acid-base imbalances are common among critically ill pediatric patients in PICU. Thus, early evaluation and recognition of acid-base and electrolyte imbalances are crucial in order to prevent poor outcomes in these patients.